Application Of Student Team Achievement Division Learning Model Assisted Teaching Props On Problem Solving - Fadilah, Nurul; Wijayanti , Rica (FKIP Universitas Halu Oleo, 2024)
The lack of students' ability to solve math problems often occurs in various schools, both at the elementary until even high school / vocational level. Through interviews conducted with one of the math teachers at SMK Ibnu Cholil stated that this also happened to class X students. This is due to the lack of use of facilities such as learning media during the learning process and the learning model applied still uses the guided inquiry model at each meeting, resulting in students becoming bored. The purpose of this study is to prove whether the STAD assisted by Trigonometric Finger Board Props can help students solve math problems or not. The experimental research used in this research is True Experimental Design with the form of Pretest-Posttest Control Group Design, this test is carried out twice, namely before research (Pretest) and after research (Posttest). The application of the STAD type cooperative learning model assisted by trigonometric fingerboard props can help students in problem solving. This can be seen from the students' learning outcomes in the form of pretest and posttest which experienced a significant increase at α = 0.000 than students who received conventional learning models.